PERKEMBANGAN MUSIK ROCK DI KOTA MALANG TAHUN 19702000-AN: KAJIAN GLOBALISASI DAN EKSISTENSI SOSIAL-BUDAYA - Yovi Ardivitiyanto (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2015)
This article aims to describe the development of rock music in Malang in 1970s 2000s. On the other hand, this article aims to look at the effect of the existence of rock music as a popular culture for socio-cultural life of youth in Malang in 1970s2000s. Writing this article is done by using the historical method, in which besides using secondary sources, primary sources are also used, such as contemporary newspaper, contemporary magazines, and oral sources. Rock music is a part of popular culture products that began developing in the 1970s. Young people become consumers of the existence of rock music continuing to be entrenched in the late 1970s. Rock music was neither present nor taken for granted, but through a journey of existence from time to time. The existence of rock music can be seen through the stages and the recording industry. Of the existence of rock music appeared a form of lifestyle inflences, which in turn was followed by its fans. On the other hand, the role of the mass media was highly effiient for the spread of a form of popular culture. Eventually the genre is able to spread widely throughout the world, including in Indonesia.Keywords: history of development, rock music, existence, popular culture